Biblical Reflections of the Struggle for Philistia at the End of the Eight Century В. С. Analysis of Chosen Passages of the Book of Isaiah - Kарera, Zdzisław J.
Prace Historyczne Z.70; ersch. 1984; poln. Résumé; assyr. Expansion usw.